Studi Etnobotani Manten Kopi sebagai Kearifan Lokal di Perkebunan Kopi Kawisari Blitar: Ethnobotanical Study of Manten Coffee as Local Wisdom in Kawisari Coffee Plantation Blitar - Aristawidya, Rifdah; Agustin, Eva Putri; Permata Sari, Dita Putri (Life Science, 2025)
Manten kopi is a traditional ritual practiced at Kawisari Plantation, Blitar, symbolizing coffee beans as a "couple" united through ceremonial processes. This study identifies the types of plants and plant parts used in the ritual, analyzes its philosophical significance, and identifies the local knowledge associated with the tradition at Kawisari Coffee Plantation, Blitar. The research employs a qualitative design with a survey method. Data were gathered through interviews and observations, with informants chosen using purposive sampling. The participants included ritual leaders and coffee farmers. The findings reveal that 11 plant species are utilized in the ritual, including coffee (Coffea sp.), pisang raja (Musa paradisiaca var. Sapientum), rice (Oryza sativa), jasmine (Jasminum sambac), champak (Michelia champaca), ylang-ylang (Cananga odorata), rose (Rosa sp.), tobacco (Nicotiana tabacum), croton (Codiaeum variegatum), coconut (Cocos nucifera), and banyan (Ficus benjamina). The plant parts used comprise leaves and flowers (36.36%), fruits (18.18%), and seeds (9.09%). The manten kopi ritual holds philosophical significance as an expression of gratitude for an abundant harvest and a hope for better harvests in the future. It reinforces cultural, spiritual, and agrarian values while preserving local wisdom to maintain harmony between humans, nature, and culture.